Kuhn’s Theory of Incommensurability: A Special Reference to Theory of Meaning - Varghese, Shabin (Tattva Journal of Philosophy, 2021)
The Structure of Scientific Revolution (1962) is the famous work by Thomas Kuhn which challenged traditional understanding of science and philosophy of science. His research activities are wide-ranging; central to his notion of incommensurability are the ideas of meaning variance and lexicon, and the impossibility of translation of terms across different theories. It is closely related to the linguistic analysis of scientific language. The schematic nature of Kuhn’s work and his ongoing clarification of its key concepts fostered additional problems of understanding, interpretation, and attribution. This paper analyses the notion of scientific language in the context of incommensurability with special reference to the theory of meaning. Linguistic experts have not attempted to incorporate Kuhn’s incommensurability to address the issues related to epistemology. This Paper shows how Kuhn’s theory of incommensurability can be applied to linguistics to overcome the problems that arise due to similar lexical terms. It argues that Kuhn’s epistemological analysis of incommensurability, particularly the challenge of understanding the process of symbolization in scientific theories, when applied to linguistics can revolutionize the discipline itself which fills the existing knowledge gap.